Cassini’s CDA observes a variety of dust populations just outside Saturn’s main rings - Linti, Simon; Khawaja, Nozair A.; Hillier, Jon; Nölle, Lenz; Fischer, Christian; Hsu, Hsiang-Wen; Srama, Ralf; Postberg, Frank (Monthly notices of the Royal Astronomical Society, 2024)
Before the end of its mission, the Cassini spacecraft orbited Saturn in a series of highly inclined elliptical ‘Ring-Grazing’ orbits (RGO). During the RGO, the spacecraft passed repeatedly through the ring plane outside the F ring, near the orbits of Janus and Epimetheus, at an average relative speed of ∼20 km s-1. For the first time, Cassini’s Cosmic Dust Analyser (CDA) directly sampled dust particles from this region. Here, we analyse the compositions of dust grains sampled within ±15 min relative to nine ring plane crossings of the RGO. The compositions of most analysed RGO grains are similar to those of E ring ice grains, implying that the E ring extends to within at least 2.45 Saturn radii (RS) of Saturn. The compositional distribution of these grains point at a similar average period (decades) since ejection from Enceladus as of particles in the outer E ring (beyond 8 RS). Higher fractions of larger grains are found near the orbits of Janus and Epimetheus, which probably represent ejecta from these moons. Most of these grains have compositions similar to the background E ring grains, indicating that E ring material is coating the surfaces of Janus and Epimetheus. We also report the detection of several types of mineral grains on prograde orbits, one of which, a water ice/silicate mixture, has never been observed by CDA elsewhere. These mineral grains appear to have a different origin from the E ring, and may arise from nearby moons, the F ring, or main rings.